Analysis of the disaster characteristics of the M6.2 earthquake occurring in Jishishan County, Gansu Province, China, in 2023 - Mingyong Lu; Xiaoxia Zhao; Jianping Wang; Kang Liu; Jing Li; Jianhua Xu; Jiyuan Yan; Xuehua Zhang (地震科学进展, 2025)
A M6.2 earthquake (35.7°N, 102.79°E) occurred at 23:59 on December 18, 2023, in Jishishan County, Linxia Prefecture, Gansu Province, China. The waves spread widely causing extensive casualties and damage to buildings. This study was conducted to analyze the associated disaster characteristics. The results showed that the earthquake occurred on sedimentary strata late at night in winter in the border area between the Loess Plateau and the Qinghai-Tibet Plateau within the Yellow River Basin. The source of the earthquake was shallow, and it was intense and destructive. Buildings in the area have low fortification levels, if any, and the population density within the earthquake area is dense, resulting in heavy casualties and significant property loss. Suggestions were made following the earthquake disaster response and the level of earthquake-resistant buildings has been appropriately improved and disaster prediction and the emergency response capacity enhanced. Future site selections for housing should avoid fault and river impact siltation areas. In the future, disaster areas will be more prone to landslides, collapses, debris flows, and other geological disasters, especially during the rainy summer season.